Changes in Eutectic Silumin Structure Depending on Gate Geometry and Its Effect on Mechanical Properties of Casting - Majernik, Jan; Gaspar, Stefan; Gryc, Karel; Socha, Ladislav (Manufacturing Technology Journal, 2018)
The gate geometry has a direct influence on casting properties. It was proven that changes in gate dimension (height) influence the permanent deformation values and die cast porosity. The present paper discusses the issue whether changes in gate dimension may affect the structural composition of eutectic silumin. It presents results of the microsection analysis of samples taken from castings made with different gate dimensions to compare the phase α and phase β proportion forming eutecticum. Consequently, conclusions are drawn to examine the influence of gate dimensions on the cast eutectic structure as well as the structure correlation and the selected mechanical properties.
Keywords: high pressure die casting; mechanical properties; eutectic structure; gate